Microencapsulation of ginger (Zingiber officinale) extract by spray drying technology. (July 2016) - Simon-Brown, Kelly; Solval, Kevin Mis; Chotiko, Aranee; Alfaro, Luis; Reyes, Vondel; Liu, Chen; Dzandu, Bennett; Kyereh, Emmanuel; Goldson Barnaby, Andrea; Thompson, Ian; Xu, Zhimin; Sathivel, Subramaniam
Abstract: The aim of this study was to evaluate the effect of microencapsulation of ginger ( Zingiber officinale Roscoe) extract using maltodextrin (MD) and/or gum arabic (GA) as microencapsulation agents on its 6-gingerol content, total phenolic and antioxidant activity. Four slurries containing 95 mL/100 mL of ginger extract (2 g solids/100 mL) and 5 g/100 mL of a blend of maltodextrin:gum arabic of weight ratios (4:1, 1:4, 5:0, and 0:5 g:g) were prepared and they were separately spray dried at 160 °C inlet air temperature to produce ginger extract powders. Ginger extract contained 20.6 ± 0.2 (mg/g solids) 6-gingerol, 7.7 ± 0.6 (mg/g solids) gallic acid equivalents and had an antioxidant activity of 19.9 ± 0.8 (μmol Trolox/g solids). Microencapsulation resulted in a decline in the quantity of 6-gingerol present in ginger extract regardless of the maltodextrin and gum arabic blend. Microencapsulation of ginger extract also reduced gallic acid equivalents and antioxidant activity. Ginger extract dried with maltodextrin:gum arabic (1:4 g:g) and (0:5 g:g) had larger particle size than that dried with maltodextrin:gum arabic (4:1 g:g) and (5:0 g:g). Maltodextrin:gum arabic (4:1 g:g) and (5:0 g:g) had better morphological properties than maltodextrin:gum arabic (4:1 g:g) and (5:0 g:g). Microencapsulated ginger extract powder may be used as a novel food ingredient. Highlights: Ginger ( Zingiber officinale Roscoe) extract (GE) contains high levels of 6-gingerol. Microencapsulation process can reduce the concentration of 6-gingerol in GE. Microencapsulation process can influence the antioxidant activity of GE.